Dishonestly increasing the likelihood of winning - Shaul Shalvi (Judgment and Decision Making, 2012)
People not only seek to avoid losses or secure gains; they also attempt to create opportunities for obtaining positive outcomes. When distributing money between gambles with equal probabilities, people often invest in turning negative gambles into positive ones, even at a cost of reduced expected value. Results of an experiment revealed that (1) the preference to turn a negative outcome into a positive outcome exists when people’s ability to do so depends on their performance levels (rather than merely on their choice), (2) this preference is amplified when the likelihood to turn negative into positive is high rather than low, and (3) this preference is attenuated when people can lie about their performance levels, allowing them to turn negative into positive not by performing better but rather by lying about how well they performed.